The gates of ion channels and enzymes - Zhou, Huan-Xiang (2009)
Protein dynamics is essential for virtually all protein functions, certainly for gating mechanisms of ion channels and regulation of enzyme catalysis. Ion channels usually feature a gate in the channel pore that prevents ion permeation in the closed state. Some bifunctional enzymes with two distant active sites use a tunnel to transport intermediate products; a gate can help prevent premature leakage. Enzymes with a buried active site also require a tunnel for substrate entrance; a gate along the tunnel can contribute to selectivity. The gates in these different contexts show distinct characteristics in sequence, structure, and dynamics, but they also have common features. In particular, aromatic residues often appear to serve as gates, probably due to their ability, through side chain rotation, to effect large changes in cross section.